2020
DOI: 10.1186/s13063-020-04336-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplemental oxygen on perioperative brain natriuretic peptide concentration in cardiac risk patients – a protocol for a prosprective randomized clinical trial

Abstract: Background: Elevated postoperative N-terminal pro-B-type natriuretic peptide (NT-proBNP) concentrations are predictive for cardiac adverse events in noncardiac surgery. Studies indicate that supplemental oxygen decreases sympathetic nerve activity and might, therefore, improve cardiovascular function. Thus, we will test the effect of perioperative supplemental oxygen administration on NT-proBNP release after surgery. Methods/design: We will conduct a single-center, double-blinded, randomized trial at the Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The trial was approved by the local Institutional Review Board and was registered at ClinicalTrials.gov (NCT 03366857) and at the European Clinical Trial Database (EudraCT 2017-003714-68). The study protocol was published previously [ 11 ]. In our main trial, we did not observe a significant difference in maximum postoperative NT-proBNP concentrations between patients receiving 80% and 30% oxygen for the duration of surgery and the first two postoperative hours [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial was approved by the local Institutional Review Board and was registered at ClinicalTrials.gov (NCT 03366857) and at the European Clinical Trial Database (EudraCT 2017-003714-68). The study protocol was published previously [ 11 ]. In our main trial, we did not observe a significant difference in maximum postoperative NT-proBNP concentrations between patients receiving 80% and 30% oxygen for the duration of surgery and the first two postoperative hours [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patients in the 30% oxygen group received an inspired oxygen fraction of 0.3 throughout surgery and 3 L/min oxygen via facemask without a reservoir for the first two postoperative hours. If needed, oxygen fraction was increased at the discretion of the attending anesthetist according to a predefined algorithm [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol was published previously. 13 We obtained written informed consent from all patients before randomization. We included 82 consecutive patients enrolled into the main study and scheduled for major abdominal surgery expected to last at least 2 hours.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…If needed, oxygen fraction was increased at the discretion of the attending anesthetist according to a prede ned algorithm. 13…”
Section: Randomizationmentioning
confidence: 99%
“…In detail, a meta-analysis of 2179 patients has shown that postoperative BNP values over 92 ng/L or NT-pro-BNP over 300 ng/L were the strongest independent predictors of 30-day mortality and non-fatal myocardial infarction (MI) in patients undergoing non-cardiac surgery 1. We have previously shown that NT-pro-BNP concentrations increases significantly within the first three postoperative days in relatively healthy patients as well as in patients with cardiovascular risk factors undergoing moderate- to high-risk abdominal surgery, which we assumed reflect increased myocardial strain in the postoperative period 6 7…”
Section: Introductionmentioning
confidence: 99%